Firm registration among White- and Latino-owned employer enterprises - Michael J Pisani (Fórum Empresarial)
This study examines the scope and determinants of firm registration among employer firms of White-owned businesses (WOBs) and Latino-owned businesses (LOBs) in the US. The primary data is derived from the 2020 Stanford Latino Entrepreneurship Initiative nationally representative survey of 3,500 WOBs and 4,145 LOBs. The determinants of firm registration are derived from entrepreneur demographics and firm characteristics, utilizing a binomial logistic regression to predict the odds of group membership of (un)registered employer firms. The scope of firm registration reveals about 80% of employer firms are registered. LOBs and immigrant-owned firms outpace registration levels of WOBs and native-owned businesses. Larger employer firms by annual sales and number of employees are more likely to be registered than their smaller business counterparts.